2014
DOI: 10.1080/01635581.2015.965333
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin E From Supplements and Diet on Colonicα- andγ-tocopherol Concentrations in Persons at Increased Colon Cancer Risk

Abstract: The available evidence indicates that γ-tocopherol has more potential for colon cancer prevention than α-tocopherol, but little is known about the effects of foods and supplements on tocopherol levels in human colon. This study randomized 120 subjects at increased colon cancer risk to either a Mediterranean or a Healthy Eating diet for six months. Supplement use was reported by 39% of the subjects, and vitamin E intake from supplements was 2-fold higher than that from foods. Serum α-tocopherol at baseline was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Maternal use of vitamin E supplements may also increase the body reserves of this micronutrient. Li et al (44) found that α-tocopherol supplements have a higher impact on tissue levels of α-tocopherol than dietary α-tocopherol. Studies on maternal supplementation of vitamin E after delivery and its effect on breast milk are scarce and inconclusive; some found a correlation between supplementation and breast milk α-tocopherol concentration and some did not (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Maternal use of vitamin E supplements may also increase the body reserves of this micronutrient. Li et al (44) found that α-tocopherol supplements have a higher impact on tissue levels of α-tocopherol than dietary α-tocopherol. Studies on maternal supplementation of vitamin E after delivery and its effect on breast milk are scarce and inconclusive; some found a correlation between supplementation and breast milk α-tocopherol concentration and some did not (14) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the IOM report points out the need for more research to determine the levels and types of tocopherols that are important for optimal nutrition and their mechanisms in the prevention of aging related chronic diseases. In particular, serum levels of γ-tocopherol appear to be independent of dietary intake and physiologically regulated [8], possibly as a consequence of chronic inflammation. This was suggested by the positive associations of γ-tocopherol with circulating C-reactive protein (CRP) and urinary isoprostane (both indicators of chronic inflammation) [9] as well as by animal and cell studies showing γ-tocopherol levels increase in response to inflammation [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant approach aims at scavenging ROS in cancer cells, thus inhibiting pro-survival signalling [230]. This approach includes dietary and supplementary antioxidants [231][232][233][234][235], glutathione (GSH)-inducing phytochemicals [236,237], NADPH oxidase inhibitors [238] or modifying cyclic nitroxides, which present a group of stable radicals with strong antioxidant properties [239]. Conversely, a pro-oxidant approach boosts ROS to cytotoxic levels, overcoming antioxidant systems and inducing cancer cell death [230,240].…”
Section: Targeting the Ros/hif Axismentioning
confidence: 99%
“…Antioxidant approach intake of antioxidants vitamins A [231], C [232] [233] and E [234], selenium [235] NADPH oxidase inhibition histamine [238] GSH induction sulforaphane [236,237] nitroxide compound manipulation tempol [239] Pro-oxidant approach ROS generation arsenic trioxide [249], imexon [248], doxorubicin, daunorubicin [250], cisplatin, oxaliplatin [251], sunitinib [252], gefitinib, erlotinib [253], trastuzumab [254], bevacizumab [255] GSH depletion β-phenylethyl isotiocyanate [241], buthionine sulfoximine [242] thioredoxin inhibition PX-12 [243], motexafin gadolinium [244] superoxide dismutase inhibition 2-methoxyestradiol [245], ATN-224 [246], disulfiram [247] In this regard, efforts have been made to develop anti-cancer therapeutics specifically targeting the HIF-1α regulation pathway, which is crucial for the survival of tumour cells. Multiple methods of targeting HIF-1α have been explored, including inhibition of HIF-1α (i) mRNA expression [257], (ii) protein synthesis [258][259][260][261][262][263][264][265][266], (iii) stabilisation [267][268][269][270], (iv) dimerization [271], (v) DNA binding [272], (vi) transcriptional activity…”
Section: Ros Modulating Strategies Compounds Involved In Cancer Clinical Trialsmentioning
confidence: 99%